The work‐habits intervention model: A 12‐month study to change work‐email habits. Issue 4 (16th July 2021) - Russell, Emma; Daniels, Kevin; Jackson, Thomas W.; Fullman, Marc
Abstract : We present a Work‐habit Intervention Model (WhIM) to explain and predict how to change work‐habits to be more effective. Habit change has primarily been researched within the health domain. The WhIM contributes a unique theoretical perspective by: (i) suggesting that work‐habit change requires a two‐stage process of exposure to regular rationalized plans and a stated intention to use these plans; and, (ii) defining effective work‐habit change in terms of improvements to both goal attainment and well‐being over time. Self‐regulatory resources are included as potential moderators of habit change. This approach implies that work‐habits (unlike health‐habits) are seldom constitutionally 'good' or 'bad', which means that change requires a clear rationale in terms of improving goal attainment and well‐being. The WhIM was evaluated in a 12‐month wait‐list intervention study designed to improve work‐email habits for workers in a UK organization ( N = 127 T1; N = 58 T3; N = 46 all data). Findings were that the two‐stage process changed work‐email habits for those with higher levels of self‐efficacy, which predicted well‐being in terms of reduced negative affect (via perceived goal attainment). We outline theoretical and practical implications and encourage future research to refine the WhIM across a range of other work contexts. Practitioner points: Workers need to regularly engage with rationalized plans of action and state their intention to use these, in order to change work‐email habits. Organizations should consider training workers to enhance their self‐efficacy prior to implementing a work‐email habit change intervention. Providing regular feedback about the impact of work‐email habit change on well‐being and goal attainment is likely to make the change sustainable in the long‐term.